ANALYSIS OF THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON PRODUCT PURCHASE DECISIONS - Hertina, Dede; Cahyadi, Ageng; Munandar, Aris; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
In line with the times, many manufacturers or companies are increasingly improving the quality of production and increasing product sales as much as possible. Currently, companies or manufacturers continue to improve and are committed to influence consumer decisions in choosing products. This study aims to determine the influence of brand image, product quality and service quality on consumer purchasing decisions in Aspa.id. This research method uses quantitative approach using associative and causal techniques. The number of samples studied was 150 respondents. The data obtained from this study, then analyzed using statistics with Instrument Test, Classic Assumption Test, Multiple Linear Analysis, Hypothesis Test, and Determination Coefficient.